Influence of nanocellulose on mechanics and morphology of polyvinyl alcohol xerogels - Pramanik, R.; Ganivada, B.; Ram, Farsa; Shanmuganathan, Kadhiravan; Arockiarajan, A. (Journal of the Mechanical Behavior of Biomedical Materials, 2019)
Xerogels are porous networks of crosslinked polymers that are useful for biomedical applications such as drug delivery, scaffold engineering, tissue regeneration, cell culture and wound dressing. However, inferior mechanical properties curtail their applications to a considerable extent. Nanocellulose fibers and crystals are often added into the polymer matrix to improve their mechanical strength. Here, nanocellulose in the mass ratios of 7%, 13% and 18% are loaded into polyvinyl alcohol (PVA) matrix followed by thermo-morpho-mechanical characterization. With increase in nanocellulose content, thermal degradation occurs at a lower temperature. It is observed that addition of higher quantity of nanocellulose crystals leads to the formation of weak cellulose rich regions causing xerogel rupture. This is predominantly observed for xerogel loaded with 18% nanocellulose crystals. Similarly, addition of higher quantity of nanocellulose fibers increase brittleness of the xerogels causing fracture. This is predominantly observed for xerogel loaded with 18% nanocellulose fibers. Creep strain and stress relaxation is observed to decrease with addition of nanocellulose loading owing to molecular chain restriction and polymer chain immobility.
Keywords: Mechanics; Morphology; Nanocellulose; Xerogels

PVDF/BaTiO3 films with nanocellulose impregnation: investigation of structural, morphological and mechanical properties - Ram, Farsa; Kaviraj, P.; Pramanik, R.; Krishnan, Amrutha; Shanmuganathan, Kadhiravan; Arockiarajan, A. (Journal of Alloys and Compounds, 2020)
Polyvinylidene fluoride (PVDF) composite films have witnessed widespread applications in biomedical and flexible electronic devices in recent years. These applications require a material that has enhanced electrical properties, mechanical flexibility along with sufficient strength. A lot of research has been carried out to enhance the piezoelectric and dielectric properties of the PVDF composite films. However, the improvements in the mechanical properties of nano filler reinforced PVDF composite films has not received due attention. In this regard, the present work focuses towards enhancing the mechanical strength and load-bearing capability of PVDF, by preparing composites of PVDF films impregnated with Cellulose Nanocrystals (CNC) and Barium Titanate (BTO) nanoparticles. Solution casting method was adapted to fabricate the PVDF/BTO/CNC films. X-ray diffractograms and FTIR (Fourier Transform infrared spectroscopy) corroborate the presence of ferroelectric gamma phase in PVDF. Mechanical and viscoelastic measurements have been carried out to examine the influence of CNC and BTO nano fillers in the PVDF matrix. The addition of CNC and BTO in PVDF film has improved the mechanical strength significantly. The stress achieved for PVDF/5% BTO and PVDF/5% BTO with 0.9% of CNC at 5% strain was 17% and 130% higher than the pristine PVDF, respectively. This study can be helpful for the design engineers to meet custom/specific requirements for a myriad of end- user applications such as piezoelectric nanogenerators. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: BaTiO3; Composite films; Mechanics; Morphology; Nanocellulose; PVDF

Mechanics of soft polymeric materials using a fractal viscoelastic model - Pramanik, R.; Soni, F.; Shanmuganathan, K.; Arockiarajan, A. (Mechanics of Time-Dependent Materials, 2022)
Soft materials are known for their plethora of biomedical applications, intricate structure-property correlation and nonlinear mechanical response. Multiple length-time scale phenomena and hierarchical structure results in their nonlinearity. Phenomenological and continuum mechanical models have been developed to predict their mechanics, which have mostly been very material-specific with inability to predict the mechanics of different types of soft materials simultaneously. This shortcoming has been addressed in the present work, wherein a generic nonlinear viscoelastic model has been proposed to predict the mechanical response of hydrogels, sponges, and xerogels. A fractal derivative viscoelastic model is proposed considering a fractal Maxwell model in parallel with a nonlinear spring. In particular, this model is chosen to qualitatively mimic the material nonlinearity inherent in soft materials. The fractal dashpot in combination with the nonlinear spring accounts for the power law time-dependent rheology of generic soft materials. These two different aspects in the form of nonlinear stiffness and non-Newtonian rheology account for mechanics of most soft materials. The present model is shown to fit well the existing literature results for mechanical response of a multitude of soft material classes with different test conditions and loading rates, which is one of the salient features of the model, apart from its simplistic mathematical framework. Further, a parametric study is reported on the mechanics of nanocellulose loaded poly(vinyl alcohol) xerogel. The model predictions are observed to be in conjunction with the experimental observations.
Keywords: Mechanics; Nonlinear; Polymeric composites; Soft materials; viscoelastic